Effects of pruning intensity and nutrient spray on growth, yield and quality attributes of guava (Psidium guajava) cv. Allahabad Safeda under central Uttar Pradesh - TRIPATHI, V K; YADAV, JAY; PANDEY, SHIWANAND; KUMAR, AMIT; TRIPATHI, RIDDHIMA (The Indian Journal of Agricultural Sciences, 2025)
The present experiment was conducted during 2023 and 2024 at Chandra Shekhar Azad University of Agriculture and Technology, Kanpur, Uttar Pradesh to evaluate the effect of pruning intensity and chemical applications on growth, yield and quality parameters of guava (Psidium guajava L.) cv. Allahabad Safeda under central Uttar Pradesh. The experiment was laid out in a randomized block design (RBD) having 10 treatments including one as control, viz. three pruning levels (20%, 40% and 60% of shoot) and combinations with calcium nitrate @1%, 2% and 3% and potassium nitrate @1.5%, 3% and 4.5%. Results revealeded significant improvement in growth parameters with T9, Pruning of 40% shoot + Ca(NO₃)₂ @2.0% having maximum plant height (7.17 m), trunk girth (29.44 cm), shoot length (22.83 cm) and shoot girth (7.87 mm). Flowering and fruit set parameters were also optimized in T9, with minimum days to flower bud initiation (22.33 days), days to first flower (23.67 days), flowers dropped/shoot (4.05) and no. of fruit set/ shoot (11.58). T9 also resulted highest fruit retention/shoot (8.96), fruit width (6.12 cm), fruit length (7.12 cm), fruit weight (171.18 g) and fruit volume (266.55 cm3). Yield improvements were evident in T9 with maximum yield/tree (45.34 kg) and per hectare (11.87 t/ha). Biochemical analysis showed superior quality of fruits in T9 resulted highest TSS (9.93°Brix), lowest titratable acidity (0.16%), highest TSS: acid ratio (68.73), maximum vitamin C (235 mg/100 g), highest total sugars (8.63%) and maximum sugar: acid ratio (59.11). These results highlighted the synergistic effect of pruning and calcium nitrate in enhancing vegetative growth, flowering, fruiting and quality attributes. This integrated approach offers the potential for optimizing guava production under sub-tropical conditions in north India.